2001
DOI: 10.2527/2001.7982152x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary conjugated linoleic acid alters fatty acid composition of pig skeletal muscle and fat.

Abstract: The dietary dose responsiveness of conjugated linoleic acid (CLA) addition relative to the fatty acid profile of edible lean tissue was examined in grower pigs treated with or without porcine somatotropin (pST). Gilts and barrows were fed CLA at 0, 0.25, 0.5, 1.0, or 2.0% of diet by weight from 20 to 55 kg BW. Additional pigs were administered (pST) at 0 or 100 microg x kg BW x d(-1) and fed either 0.5 or 2.0% CLA. Animals were fed diets containing 18% CP, 1.2% lysine, and 3.5 Mcal of DE/kg at 110% of ad libit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
62
4
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 36 publications
(53 reference statements)
10
62
4
4
Order By: Relevance
“…Dietary CLA (Thiel et al 1998) or carnitine supplementation Smith et al 1994) has been shown to reduce backfat and increase carcass leanness and CrNic ) has also been shown to decrease backfat in pork carcasses. However, these effects were not observed in some other studies (Smith et al 1997;O'Quinn et al 1998;Ramsay et al 2001) or in the present experiment. This may have been the consequence of the genetic leanness of the light, market-weight gilts slaughtered in this study, the composition of the CLA mix in MTO, or the total fat content in the diet may have differed enough to cause variable response among these studies.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Dietary CLA (Thiel et al 1998) or carnitine supplementation Smith et al 1994) has been shown to reduce backfat and increase carcass leanness and CrNic ) has also been shown to decrease backfat in pork carcasses. However, these effects were not observed in some other studies (Smith et al 1997;O'Quinn et al 1998;Ramsay et al 2001) or in the present experiment. This may have been the consequence of the genetic leanness of the light, market-weight gilts slaughtered in this study, the composition of the CLA mix in MTO, or the total fat content in the diet may have differed enough to cause variable response among these studies.…”
Section: Discussioncontrasting
confidence: 53%
“…We also observed an improvement in belly firmness in MTO-supplemented pigs. The mechanism for the actions of CLA in pigs is explained by Ramsay et al (2001). These authors found increased percentages of palmitic and stearic acids in backfat from swine fed CLA, which indicated ∆ 9 stearoyl-CoA desaturase was inhibited.…”
Section: Discussionmentioning
confidence: 95%
“…Our results would imply that the differences in fat deposition in pigs fed betaine 1 CLA (Ferná ndez-Fígares et al, 2008) could not be explained by dissimilar availability of glucose for lipogenesis. Similarly, CLA did not alter plasma glucose and insulin in growing (Ramsay et al, 2001) and finishing pigs (Ostrowska et al, 2002) or lactating sows (Bontempo et al, 2004). Nevertheless, serum glucose concentration was decreased in finishing pigs (Huang et al, 2006) fed betaine-supplemented diets, the effect being ascribed to increased insulin levels.…”
Section: Discussionmentioning
confidence: 84%
“…There is also evidence that CLA suppresses PUFA desaturases and elongase in cell systems (Chuang et al, 2001a,b;Eder et al, 2002), and CLA decreased C 18 PUFA in pig muscle and fat (Ramsay et al, 2001), and DHA in chicken tissues (Yang et al, 2003). Decreased tissue PUFA levels after feeding CLA has been reported in yellow perch and tilapia (Twibell et al, 2001;Yasmin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, CLA decreased the activity and gene expression of stearoyl coenzyme A desaturase (SCD) (Choi et al, 2001(Choi et al, , 2002, and dietary CLA increased saturated fatty acids and decreased 18:1 and monoenes in pig muscle and fat (Ramsay et al, 2001). In the present study, increased proportions of 18:0 and decreased 18:1n-9 were observed in flesh and, especially, liver of cod fed CLA suggesting inhibition of Δ9 desaturation.…”
Section: Discussionmentioning
confidence: 99%